Question
Asked Dec 4, 2019
2 views
Use the chain rule with the power rule
Question
Consider the function g(x) = (f(x)). If f(4) = 3 and f' (4) = -2, then find g'(4).
Provide your answer below:
help_outline

Image Transcriptionclose

Use the chain rule with the power rule Question Consider the function g(x) = (f(x)). If f(4) = 3 and f' (4) = -2, then find g'(4). Provide your answer below:

fullscreen
check_circle

Expert Answer

star
star
star
star
star
1 Rating
Step 1

Given function:

g(x)(f(x))(4) = 3 and f'(4)-2
To find g'(4)
s()- ())
((s()
help_outline

Image Transcriptionclose

g(x)(f(x))(4) = 3 and f'(4)-2 To find g'(4) s()- ()) ((s()

fullscreen
Step 2

Apply the chai...

f = u,u=f(x)
-(u')(x)
(u)=5u
Su' f'(x)
help_outline

Image Transcriptionclose

f = u,u=f(x) -(u')(x) (u)=5u Su' f'(x)

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Calculus

Other